Unraveling India's malnutrition dilemma: A path toward nutrition-sensitive agriculture - Pingali, Prabhu; Abraham, Mathew (International Food Policy Research Institute, 2019)
In this chapter, we make the case for India to shift to a nutrition-focused agricultural sector that goes beyond staple grain productivity to emphasize the production and consumption of micronutrient-rich foods. The chapter first reviews the nutrition trends in India, characterized by slow progress in addressing high and variable rates of malnutrition. It then assesses the policies that have influenced agricultural growth trajectories and safety-net programs to highlight the major challenges and disconnects in agriculture and nutrition policy. Finally, it calls for integrating some elements that a food-systems approach would consider, such as income, availability of nutritious food, intra-household distribution, and the health environment, as a way forward in addressing India’s malnutrition dilemma.